Private health care sector in Croatia : is private spending on health care myth or reality? - Kovač, Nevenka, liječnica (Array, 2021)
This paper investigates the trends in business activity of the private health care sector in Croatia from 2011 to 2018. Databases of Croatian provider of financial and electronic services - Financial Agency (FINA) - have been employed to explore key performance indicators of private health care sector companies, in particular trends in total employment, business revenues and operating profits. In addition, the most important features of voluntary health insurance (VHI) provided by private health insurance companies and the Croatian Health Insurance Fund (HZZO) have been presented. Furthermore, this paper provides both a relevant analysis of the private health care sector as well as private spending on health care in Croatia. The results indicate that users of health care services are willing to pay more to gain faster access and higher quality services. In 2018, expenditures for private health care services reached almost HRK 5 billion. Nearly 60% were out-of-pocket (OOP) payments and 40% were paid through the VHI. Despite the persistent recession, the private health care sector in Croatia experienced an average annual growth rate of 10% in the analysed period. More recently, the trend of introduction of more complex services within private providers can be observed indicating the rise in investments, and competitiveness. In conclusion, private health care sector"s presence in Croatia is a reality that should be addressed adequately. Original findings in this paper might serve as starting point for future discussions regarding the private health care sector role in the overall health care system financing. The paper brings a deeper insight into Croatian private health care sector market using original and most recent microdata thus shedding the light on important part of our health economy. Nevertheless, paper has certain limitations that are mainly reflected in relatively narrow set of indicators used in private health care sector business analysis.